The predictive value of the assessment of medicinal sensitivity in colorectal cancer - Smalyakova, Raisa M. (Journal of the Belarusian State University. Ecology, 2019)
The expression of TYMS, TYMP, ERCC1, OPRT and DPD genes, which characterizes medicinal sensitivity to platinum and fluoropyrimidine medicines in patients with colorectal cancer, is analyzed. A complex molecular genetic assessment of the expression levels of the TYMS and TYMP 5-fluorouracil metabolism genes allows patients to be stratified into a group with high chemoresistance and the risk of disease progression in order to select a second-line adjuvant cytostatic therapy. A significant correlation was established between the levels of TYMP, OPRT, DPD gene expression and the extent of the tumor process, the presence of metastases in colorectal cancer. The expression of the TYMS, TYMP and OPRT genes correlates with the risk of disease relapse, chemotherapy, poor prognosis and reduced overall survival of patients with colorectal cancer.
Keywords: colorectal cancer; gene expression; chemosensitivity; relapse; polychemotherapy; prognosis; polymerase chain reaction; stratification